The compliance with the 2011 standards of selected secondary school library media centers in Antipolo City - Santillan, Kevin Bryan O. (School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study gathered information to determine the compliance of the selected school libraries in Antipolo City to the following sections of the 2011 Standards for Philippine Libraries for School Library Media Centers: (1) Mission, Goals, and Objectives, (2) Administration, (3) Human Resources, (4) Collection Management, (5) Services and Utilization, (6) Physical Facilities, (7) Financial Resources, and (8) Linkages and Networking. The respondents of the study were composed of head librarians and principals from () La Salle College Antipolo, (2) Nazareth Christian School, (3) The Pleasant Mount School and (4) College of San Benildo - Rizal only.